Porous Hollow Superlattice NiMn2O4/NiCo2O4 Mesocrystals as a Highly Reversible Anode Material for Lithium-Ion Batteries - Li, Lingjun; Yao, Qi; Liu, Jiequn; Ye, Kaibo; Liu, Boyu; Liu, Zengsheng; Yang, Huiping; Chen, Zhaoyong; Duan, Junfei; Zhang, Bao (Frontiers in Chemistry, 2018)
Abstract: As a promising high-capacity anode material for Li-ion batteries, NiMn2O4 always suffers from the poor intrinsic conductivity and the architectural collapse originating from the volume expansion during cycle. Herein, a combined structure and architecture modulation is proposed to tackle concurrently the two handicaps, via a facile and well-controlled solvothermal approach to synthesize NiMn2O4/NiCo2O4 mesocrystals with superlattice structure and hollow multi-porous architecture. It is demonstrated that the obtained NiCo1.5Mn0.5O4 sample is made up of a new mixed-phase NiMn2O4/NiCo2O4 compound system, with a high charge capacity of 532.2 mAh g−1 with 90.4% capacity retention after 100 cycles at a current density of 1 A g-1. The enhanced electrochemical performance can be attributed to the synergistic effects of the superlattice structure and the hollow multi-porous architecture of the NiMn2O4/NiCo2O4 compound. The superlattice structure can improve ionic conductivity to enhance charge transport kinetics of the bulk material, while the hollow multi-porous architecture can provide enough void spaces to alleviate the architectural change during cycling, and shorten the lithium ions diffusion and electron-transportation distances.